(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper attempts to investigate strategies for integrating Total Quality Management with Artificial Intelligence and employee engagement to improve the quality culture in organizations. Through an examination of qualitative reviews of previous literature and expert opinions, this research work identifies synergies that will enhance both organizational effectiveness and employee satisfaction. Four major themes are explored that AI used to improve employee involvement and quality culture. This brings employees closer to the quality objectives of an organization and, therefore, promotes a sustainable and robust quality culture because it benefits the general performance of the organization and the well-being of the employees.